2013
DOI: 10.1159/000356642
|View full text |Cite
|
Sign up to set email alerts
|

The Human Pendrin Promoter Contains two N4GAS Motifs with Different Functional Relevance

Abstract: Background: Pendrin, an anion exchanger associated with the inner ear, thyroid and kidney, plays a significant role in respiratory tissues and diseases, where its expression is increased following IL-4 and IL-13 exposure. The mechanism leading to increased pendrin expression is in part due to binding of STAT6 to a consensus sequence (N4 GAS motif) located in the pendrin promoter. As retrospective analyses of the 5' upstream sequence of the human pendrin promoter revealed an additional N4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We chose to focus on six CpG sites (91, 90, 89, 87, 86 and 85) within the pendrin promoter due to their proximity to the N 4 GAS motif that is essential for the response to IL-4 [21, 23]. The basal and IL-4 stimulated methylation patterns for these CpG sites in all four cell types are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to focus on six CpG sites (91, 90, 89, 87, 86 and 85) within the pendrin promoter due to their proximity to the N 4 GAS motif that is essential for the response to IL-4 [21, 23]. The basal and IL-4 stimulated methylation patterns for these CpG sites in all four cell types are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This upregulation is induced by phosphorylated STAT6, a transcription factor activated by IL-4, which recognises and binds to a functional N 4 GAS motif present in the pendrin promoter [21, 23]. Several CpG sites, hotspots for DNA methylation, are located between the binding motif for STAT6 and the transcription start site of the pendrin gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the SLC26A4 gene is an IL-4/IL-13-inducible molecule, it was reasonable to think that STAT6, a transcriptional factor critical for the IL-4/IL-13 signals, regulates the expression of the SLC26A4 gene. Nofziger et al found that there exist two consensus binding sites for STAT6 (TTC(N 4 )GAA) at −3472 to −3463 (motif 1) and −1812 to −1803 (motif 2) of the 5′-flanking region of the SLC26A4 gene [ 24 , 25 ]. Vanoni et al showed that although both consensus sequences can bind STAT6 following IL-4 exposure, IL-4- or IL-13-inducible pendrin expression requires only motif 2 [ 25 ].…”
Section: Discovery Of Pendrin As a Downstream Molecule Of The Il-4mentioning
confidence: 99%
“…Nofziger et al found that there exist two consensus binding sites for STAT6 (TTC(N 4 )GAA) at −3472 to −3463 (motif 1) and −1812 to −1803 (motif 2) of the 5′-flanking region of the SLC26A4 gene [ 24 , 25 ]. Vanoni et al showed that although both consensus sequences can bind STAT6 following IL-4 exposure, IL-4- or IL-13-inducible pendrin expression requires only motif 2 [ 25 ]. These results suggest that IL-4 or IL-13 induces expression of the SLC26A4 gene in a cis -regulating manner.…”
Section: Discovery Of Pendrin As a Downstream Molecule Of The Il-4mentioning
confidence: 99%